The Effect of Capital Structure on Financial Performance in Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2017-2022. - Ernawati Ridjal; Masdar Mas’ud; Asdar Djamereng (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study was conducted with the following objectives: (1) to determine and analyze the effect of the Debt to Equity Ratio (DER) on Return on Equity (ROE) in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX); (2) to determine and analyze the effect of the Debt to Asset Ratio (DAR) on ROE in food and beverage sector companies listed on the IDX; (3) to determine and analyze the effect of the Equity to Asset Ratio (EAR) on ROE in food and beverage sector companies listed on the IDX. This research approach is quantitative, specifically causal-comparative research, using secondary data from financial reports. The population in this study consists of 84 companies, and using purposive sampling techniques, a sample of 22 companies over a period of 3 years was obtained. Data analysis was conducted using multiple linear regression analysis with the help of Statistical Package for the Social Sciences (SPSS 25) software. The results of this study indicate that (1) DER has a negative and significant effect on ROE in manufacturing companies in the food and beverage subsector listed on the IDX; (2) capital structure with the DAR variable has a positive and significant effect on ROE in manufacturing companies in the food and beverage subsector listed on the IDX; (3) EAR has a negative and significant effect on ROE in manufacturing companies in the food and beverage subsector listed on the IDX.